1998
DOI: 10.1086/517379
|View full text |Cite
|
Sign up to set email alerts
|

High Human Immunodeficiency Virus Type 1 RNA Load in the Cerebrospinal Fluid from Patients with Lymphocytic Meningitis

Abstract: Thirty-seven matched cerebrospinal fluid (CSF) and plasma samples from 34 human immunodeficiency virus type 1 (HIV-1) -infected patients with suspected meningitis were analyzed for levels of HIV-1 RNA and markers of inflammation. Patients with tuberculous (n Å 9) or cryptococcal (n Å 6) meningitis had the highest CSF virus loads, which in many cases exceeded the levels in plasma, compared with patients with meningococcal meningitis (n Å 3), aseptic meningitis (n Å 8), tuberculoma (n Å 2), or AIDS dementia comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 13 publications
9
33
0
1
Order By: Relevance
“…However, Cryptococcus neoformans induces HIV-1 replication and enhances HIV infectivity in vitro (147,267) and cryptococcal meningitis leads to an increased HIV-1 load in cerebrospinal fluid (241). It is also likely that inflammatory stimuli of any etiology, if of sufficient intensity, will upregulate HIV-1 replication in vivo.…”
Section: Other Inflammatory Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…However, Cryptococcus neoformans induces HIV-1 replication and enhances HIV infectivity in vitro (147,267) and cryptococcal meningitis leads to an increased HIV-1 load in cerebrospinal fluid (241). It is also likely that inflammatory stimuli of any etiology, if of sufficient intensity, will upregulate HIV-1 replication in vivo.…”
Section: Other Inflammatory Stimulimentioning
confidence: 99%
“…It is suggested that induction of successive increases in systemic HIV-1 load may lead to more rapid deterioration in the already impaired immune system and may also hasten the appearance of mutant viruses that may escape the established antiviral mechanisms. The plasma HIV-1 load is a major indicator of the prognosis (229), and there is abundant evidence that exogenous immune-activating stimuli cause increases in HIV-1 replication in blood (38,41,125,234,250,255,290,319,320,326), in tissues (56,249,254,319), and in anatomical compartments (37,62,193,241,245). However, the epidemi-ological evidence to support the hypothesis that immune-activating stimuli also accelerate HIV-1 disease progression in the longer term is less clear.…”
Section: Immune Activation and Hiv-1 Disease Progressionmentioning
confidence: 99%
“…Entry of HIV-1 into the brain involves the interaction of several factors such as HIV proteins, cytokines, chemokines, and adhesion molecules (33,88,94) and is proposed to occur early in the progression of AIDS (84,101). Patients with HIVE show tight junction disruption (18) and increased endothelial cell DNA fragmentation (107).…”
Section: Haart and The Brainmentioning
confidence: 99%
“…The transport of C. neoformans through the brain and its effect on the BBB have not yet been described. Only one study by Morris et al (1998) described that of nine AIDS patients with C. neoformans meningitis, only three showed an alteration of BBB. These data suggested that, in our model, C. neoformans could provoke a rupture of tight junctions allowing ITC to cross BBB by paracellular transport without affecting transcellular transfer.…”
Section: Modulation Of Efflux In Cerebral Transport Of Itraconazolementioning
confidence: 99%